Contratualização na Atenção Primária à Saúde: a experiência de Portugal e Brasil - Vanessa Costa e Silva (Ciência & Saúde Coletiva, 2014)
The contractual arrangements adopted in the Family Health Strategy are a topic as yet scantly addressed in studies. It is introduced in Brazil in different models in accordance with the contracting entity and the legal status of the contracted service provider; and in Portugal, it is based on a model of inter-governmental contrac- tual arrangements with the Family Health Units. In this paper, the current status of contractual arrangements in both countries is presented and their attributes of joint planning, accountability with autonomy and performance-based incentive programs are discussed. The main contributions are: better coordination of the health organizations; substitution of the hierarchical command-control logic with greater participation; and accountability of professionals with enhanced performance of their activities. The conclusion reached is that one of the facilitating elements is gradual construction, in an environment of ongoing learning, with health professionals playing the leading role. However, the major challenges include transparency in the im- plementation of processes, the enforcement of sound auditing mechanisms and information systems, as well as the continuous review of indicators and their suitability for the health needs of the population.